P2 receptors and platelet function - Hechler, Béatrice (Springer Netherlands, 2011)
Following vessel wall injury, platelets adhere to the exposed subendothelium, become activated and release mediators such as TXA(2) and nucleotides stored at very high concentration in the so-called dense granules. Released nucleotides and other soluble agents act in a positive feedback mechanism to cause further platelet activation and amplify platelet responses induced by agents such as thrombin or collagen. Adenine nucleotides act on platelets through three distinct P2 receptors: two are G protein-coupled ADP receptors, namely the P2Y(1) and P2Y(12) receptor subtypes, while the P2X(1) receptor ligand-gated cation channel is activated by ATP. The P2Y(1) receptor initiates platelet aggregation but is not sufficient for a full platelet aggregation in response to ADP, while the P2Y(12) receptor is responsible for completion of the aggregation to ADP. The latter receptor, the molecular target of the antithrombotic drugs clopidogrel, prasugrel and ticagrelor, is responsible for most of the potentiating effects of ADP when platelets are stimulated by agents such as thrombin, collagen or immune complexes. The P2X(1) receptor is involved in platelet shape change and in activation by collagen under shear conditions. Each of these receptors is coupled to specific signal transduction pathways in response to ADP or ATP and is differentially involved in all the sequential events involved in platelet function and haemostasis. As such, they represent potential targets for antithrombotic drugs.